Research Progress and Development Trends in Energy- Field-Assisted Laser Additive Manufacturing of Titanium Alloys - Ma, Lixiang (Exploring Science Academic Conference Series, 2026)
Titanium alloys are known for their high specific strength, excellent corrosion resistance, and good high - temperature mechanical properties. They have extensive applications in fields such as aerospace, high -end equipment, and biomedicine. However, during the laser additive manufacturing of titanium alloys, rapid melting and solidification behavior, combined with complex thermal cycling, tend to induce coarse columnar grain structures, residual stress accumulation, and defects such as porosity and cracks. I t constrains further improvement in the comprehensive performance of the components. In recent years, energy -field-assisted technologies have emerged as a crucial approach to enhancing the quality and performance of laser additive manufacturing of titanium alloys. By introducing external fields, such as ultrasonic, thermal, plastic deformation, and electromagnetic fields, during the forming process, these technologies enable effective control over molten pool flow, heat and mass transfer, and the evolution of solidified microstructures. This paper provides a comprehensive review of research progress on laser additive manufacturing of titanium alloys assisted by single and multi -energy fields. It focuses on summarizing the process characteristics, microstructure control mechanisms, and performance enhancement principles associated with various energy fields, while elucidating the underlying mechanisms by which these fields influence molten pool evolution, grain refinement, defect suppression, and residual stress regulation. Finally, the future development directions of energy-field-assisted laser additive manufacturing of titanium alloys are outlined. This paper provides a theoretical reference for the development and engineering application of additive manufac turing technology for titanium alloys.